Long-Haul Northeast Travel Disrupts Sleep and Induces Perceived Fatigue in Endurance Athletes - Stevens, Christopher J.; Thornton, Heidi R.; Fowler, Peter M.; Esh, Christopher; Taylor, Lee (Frontiers in Physiology, 2018)
Introduction: Long-haul transmeridian travel is known to cause disruptions to sleep and immune status, which may increase the risk of illness. Aim: This study aimed to determine the effects of long-haul northeast travel for competition on sleep, illness and preparedness in endurance athletes. Methods: Twelve trained (13.8±3.2 training h/week) masters (age: 48±14 y) triathletes were monitored for sleep (quantity via actigraphy and quality via self-report), mucosal immunity (salivary immunoglobulin-A) and stress (salivary cortisol) as well as self-reported illness, fatigue, recovery and preparedness. Baseline measures were recorded for 2 weeks prior to travel for all variables except for the saliva samples, which were collected on three separate days upon waking. Participants completed normal training during the baseline period. Measures were subsequently recorded before, during and after long-haul northeast travel from the Australian winter to the Hawaiian summer, and in the lead up to an Ironman 70.3 triathlon. Results: All comparisons are to baseline. There was a most likely decrease in sleep duration on the over-night flight (-4.8±1.2 hours; effect size; ±90% confidence limits = 3.06; ±1.26) and a very likely increase in sleep duration on the first night after arrival (0.7±1.0 hours; 1.15; ±0.92). After this time, sleep duration returned to baseline for several days until it was very likely decreased on the night prior to competition (-1.2±1.0 hours; 1.18; ±0.93). Nap duration was likely increased on the first day after arrival (36±65 min; 3.90; ±3.70). There was also a likely increase in self-reported fatigue upon waking after the first night in the new destination (1.1±1.6 AU; 0.54; ±0.41) and there were three athletes (25%) who developed symptoms of illness 3-5 days after arrival. There were no changes in sleep quality or mucosal measures across study. Discussion: Long-haul northeast travel from a cool to a hot environment had substantial influences on sleep and self-reported fatigue, but these alterations had returned to pre-departure baseline 48 hours after arrival. Endurance athletes undertaking similar journeys may benefit from optimizing sleep hygiene, especially on the first two days after arrival, or until sleep duration and fatigue levels return to normal.